2019
DOI: 10.1016/j.joca.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

3D bone-shape changes and their correlations with cartilage T1ρ and T2 relaxation times and patient-reported outcomes over 3-years after ACL reconstruction

Abstract: Purpose: (1) To identify bone-shape changes from baseline to 3-years after anterior cruciate ligament reconstruction (ACLR). (2) to assess association between changes in bone-shape from baseline to 6-months and changes in cartilage matrix and patient functions and symptoms from baseline to 3-years after ACLR. Methods: Bilateral knees of 30 patients with unilateral ACL injuries were scanned at baseline, 6-months, 1-, 2-, and 3-years after ACLR. Bilateral knees of 13 controls were scanned at baseline, 1-and 3-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 15 publications
1
36
1
Order By: Relevance
“…The trajectories of changes in the knee's shape during the 4-year period appeared to be stable in an older population. This finding differs in some ways from the findings of prior studies, primarily that of Zhong et al [50], who reported changes in the knee's shape within 3 years after ACL reconstruction. However, that study differs from the current one in many ways; bone shape remodeling occurred in the context of a joint injury, and the age of the participants was much younger than that in the current study (mean age of approximately 30 years versus a mean age of almost 60 years).…”
Section: Does the Shape Of The Knee Segregate Stably Into Different Gcontrasting
confidence: 99%
See 1 more Smart Citation
“…The trajectories of changes in the knee's shape during the 4-year period appeared to be stable in an older population. This finding differs in some ways from the findings of prior studies, primarily that of Zhong et al [50], who reported changes in the knee's shape within 3 years after ACL reconstruction. However, that study differs from the current one in many ways; bone shape remodeling occurred in the context of a joint injury, and the age of the participants was much younger than that in the current study (mean age of approximately 30 years versus a mean age of almost 60 years).…”
Section: Does the Shape Of The Knee Segregate Stably Into Different Gcontrasting
confidence: 99%
“…Multiple studies using statistical shape modeling have found that there are sex-related differences in knee shape in individuals with and without knee OA [2,30,34,42,45], but these have all evaluated bone shape at a single timepoint. A few published studies described change in the knee's shape over time [20,35,50]; however, none of these trajectory-related statistical shape modeling studies examined the relation of sex to change in bone shape over time. This may be because all of the studies had relatively small numbers of participants and likely did not have power to identify sex-related differences.…”
Section: Do Females and Males Have Different Trajectories Of Bone Shamentioning
confidence: 99%
“…Zhong et al used statistical shape modeling of knee MRI to document changes in medial femoral condyle shape, intercondylar notch width, tibia plateau area, and medial tibia slope in 30 subjects following ACL reconstruction. Increases in intercondylar notch width and lateral tibia plateau area were associated with increases in cartilage T2 and T1-rho relaxation time between baseline and 3 year follow-up 82 .…”
Section: Osteoarthritis Andcartilagementioning
confidence: 85%
“…In the later study, mechanical tests revealed a 19% increase in tibial articular cartilage thickness 3 months after injury and this supports our finding of a 14% increase in thickness (calculated as a mean increase in thickness of 0.4 mm relative to a mean 2.8 mm thick cartilage obtained from normal knees at the same location). Our measurements were taken soon after injury (mean 17 days) and are concerning as there is a strong evidence that the articular cartilage and its matrix components change soon after ACL injury, reconstruction and return to activity . In addition, following severe knee trauma that involves the ACL, increased T1ρ and T2 relaxation times are thought to reflect loss of proteoglycan and change in water content that precede changes to cartilage thickness associated with the progression of PTOA.…”
Section: Discussionmentioning
confidence: 99%
“…Our measurements were taken soon after injury (mean 17 days) and are concerning as there is a strong evidence that the articular cartilage and its matrix components change soon after ACL injury, reconstruction and return to activity. 23,[35][36][37][38][39][40] In addition, following severe knee trauma that involves the ACL, increased T1ρ and T2 relaxation times are thought to reflect loss of proteoglycan and change in water content that precede changes to cartilage thickness associated with the progression of PTOA. This may be the underlying mechanism associated with cartilage thickening that was observed in the current study.…”
mentioning
confidence: 99%